Validation of content and appearance of an educational manual to promote children's mental health - Marina Nolli Bittencourt; Raissa dos Santos Flexa; Ingrid de Souza Reis Santos; Larissa Duarte Ferreira; Camila Rodrigues Barbosa Nemer; José Luiz da Cunha Pena (Universidade Federal do Ceará, 2020)
Objective: to validate the content and appearance of an educational manual to promote children's mental health. Methods: this is a methodological study, in which 16 specialists (health and education professionals) and six of the target audience (nurses) participated. The Content Validity Index and the Agreement Index were calculated according to the response to the instrument, which assessed the objectives, appearance, structure, organization, relevance and didactics of the manual. Results: the Content Validity Index was 0.984 for the target audience, and the Agreement Index was 100.0%. The main changes were in the title, objectives and theoretical framework, excluding workshops and spelling and grammatical revision. Conclusion: the manual presented satisfactory Content Validity and Agreement indexes. It can assist nurses and other health professionals in promoting children's mental health, promoting the development of emotional intelligence.